Equatorial Plasma Bubble Detection using the Convolutional Neural Network (CNN) and Support Vector Machine (SVM) - Thananphat Thanakulketsarat; Pornchai Supnithi; Lin Min Min Myint; Kornyanat Hozumi (My University, 2023)
Equatorial plasma bubbles (EPB) refer to the area of low electron density in the Earth’s ionosphere near the equator during post sunset and post-midnight. They influence the radio communications and GPS signals. In this work, we study the EPB occurrences and characteristics using the VHF radar images observed at the Chumphon station, Thailand, near the magnetic equator.. We develop an EPB image detection system using a hybrid learning technique with convolutional neural network (CNN) and support vector machine (SVM) and evaluate the accuracy of the proposed CNN-SVM model using two kernels: polynomial kernel and radial basis function (RBF) kernel.
Keywords: Currency Recognition and Detection; Fault Detection and Control Systems; Anomaly Detection Techniques and Applications